Organization design - John, Joseph; Baumann, Oliver; Burton, Richard M.; Srikanth, Kannan (Advances in strategic management ;, 2018)
This volume of 'Advances in Strategic Management'explores emerging trends and contemporary research in the field of organization design. It reflects a renewed focus on the universal problems of organizingthe division of labor and the integration of effort. At the same time, it incorporates new ideas on designs for cooperation in organizations. The studies published here employ a wide variety of theories and research designs to contribute to this renewal of organization design research, considering collaborative ways of working, organizational learning, and strategic innovation.